Pedagogical Activities of Graduate (1916) of Riga Polytechnic Institute Jānis Rupais (1889–1974) in Latvia - Zigmunde, Alīda; Gudro, Ilze; Ūsele, Ilze; Bauere, Ineta (History of Engineering Sciences and Institutions of Higher Education, 2023)
The research on Jānis Rupais (1889–1974), engineer, pedagogue, and graduate of the Department of Chemistry (1916) of Riga Polytechnic Institute (RPI), was conducted using the documents of the National Archives of Latvia, the Latvian State Historical Archive and the Latvian State Archives, as well as Gulbene Municipality Museum of History and Art. The article about the well-known pedagogue in Latvia in the 20th century – the long-term and only Principal of Gulbene State Commercial School and Vocational School (1926–1944) J. Rupais also reflects on his activities after World War II at Riga Industrial Polytechnicum. It describes both the educational institutions, the principal and pedagogue J. Rupais and his work methods, and the contribution he made to Gulbene and Latvia.